Factors influencing the confidence and knowledge of nurses prescribing antiretroviral treatment in a rural and urban district in the Western Cape province - Deborah J. Solomons; Anita S. van der Merwe; Tonya M. Esterhuizen; Talitha Crowley (AOSIS, 2019)
Background: Since the introduction of nurse-initiated and managed antiretroviral treatment (NIMART) in South Africa in 2010, initiation of antiretroviral therapy (ART) in primary care has become the responsibility of nurses. The continued success of this approach is dependent on factors such as adequate training and effective support systems. Objectives: This study aimed to investigate factors influencing the knowledge and confidence of professional nurses in managing patients living with human immunodeficiency virus (HIV) in primary healthcare settings in a rural and urban district in the Western Cape. Methods: A cross-sectional survey was conducted amongst 77 NIMART-trained nurses from 29 healthcare facilities to measure demographic details, influencing factors, HIV management confidence and HIV management knowledge. Results: The majority of participants had adequate HIV management knowledge and reported being very confident or expert in the HIV management skills or competencies. Participants trained recently on local guidelines (Practical Approach to Care Kit) (3 years ago or less) had significantly higher knowledge scores. Regular feedback about clinic and personal performance was associated with higher HIV management knowledge. Participants who received NIMART mentoring over a period of 2 weeks had a higher mean confidence score compared to other periods of mentoring. A higher caseload of patients living with HIV was also associated with higher knowledge and confidence. Conclusion: Training, mentorship and clinical practice experience are associated with knowledge and confidence. Recommendations include the strengthening of current training and mentoring and ensuring that NIMART-trained nurses are provided with regular updates and sufficient opportunities for clinical practice.